Direct Laser Interference Patterning of Fluorine‐Doped Tin Oxide as a Pathway to Higher Efficiency in Perovskite Solar Cells - Heffner, Herman (2024)
Improving light-trapping capabilities through surface microstructuring of transparent conductive oxides is a promising approach to enhance solar cell efficiency. This study focuses on treating fluorine-doped tin oxide (FTO) thin films using four-beam direct laser interference patterning (DLIP) to create dot-like periodic surface microstructures. The surface analysis using scanning electron microscopy and confocal microscopy reveals the presence of a periodic square grid of microcraters with a spatial period of ≈700 nm and an average depth ranging between 4 and 18 nm. These structures enhance the dispersion of incoming light up to 1000% in the visible and NIR spectra. When integrated into metal halide perovskite solar cells, FTO films patterned using low fluence conditions lead to a notable increase in the power conversion efficiencies (PCEs) compared to those made using untreated FTO. Importantly, preliminary stability tests on devices based on patterned FTO substrates show significantly improved stability compared to those fabricated using reference unpatterned substrates. These findings demonstrate that a DLIP treatment of FTO substrates is a promising technique that can substantially enhance the efficiency and stability of perovskite photovoltaic devices.